2020
DOI: 10.1093/jee/toaa033
|View full text |Cite
|
Sign up to set email alerts
|

The Gene Introgression Approach and the Potential Cost of Genes that Confer Strong Phosphine Resistance in Red Flour Beetle (Coleoptera: Tenebrionidae)

Abstract: Resistance in pest insects to the grain fumigant phosphine (PH3) poses a threat to trade and food security. The possible pleiotropic effects of PH3 resistance on development and reproduction were investigated in the red flour beetle, Tribolium castaneum (Herbst), by introgressing two genes known to be major contributors to strong resistance (tc_rph1 and tc_rph2) into a susceptible background. The tc_rph2 allele was the G135S variant, whereas the identity of tc_rph1 allele was unknown but could have been one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
4
3
0
1
Order By: Relevance
“…While we conclude that phosphine resistant insects do not incur fitness costs in C. ferrugineus, in alignment with previous reports on three major stored product pest species, R. dominica, T. castaneum and S. oryzae (Schlipalius et al 2008;Daglish et al 2014Daglish et al , 2015Daglish et al , 2020, the observed decline in rph2 allele frequency in unselected segregating populations of T. castaneum (Jagadeesan et al 2013a) and S. oryzae (Nguyen et al 2016) needs further examination. Unfortunately, both these latter studies could not continue assessing the decline in allele frequency beyond the F 20 filial generations, and did not correlate the observed change in allele frequency in terms of developmental or reproductive traits.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…While we conclude that phosphine resistant insects do not incur fitness costs in C. ferrugineus, in alignment with previous reports on three major stored product pest species, R. dominica, T. castaneum and S. oryzae (Schlipalius et al 2008;Daglish et al 2014Daglish et al , 2015Daglish et al , 2020, the observed decline in rph2 allele frequency in unselected segregating populations of T. castaneum (Jagadeesan et al 2013a) and S. oryzae (Nguyen et al 2016) needs further examination. Unfortunately, both these latter studies could not continue assessing the decline in allele frequency beyond the F 20 filial generations, and did not correlate the observed change in allele frequency in terms of developmental or reproductive traits.…”
Section: Discussionsupporting
confidence: 90%
“…Our results supported the importance of controlling for background genetic effects, without which the significant differences observed between the Ref-R and Ref-S in developmental time and body weight could have been interpreted that phosphine resistance genes are associated with fitness costs. Daglish et al (2020) also observed significant difference in beetle weight between susceptible and resistant strains in T. castaneum, but not when the phosphine resistance trait was compared in an isogenic background, supporting the conclusion of this study. Similar results of insecticide susceptible strain having fitness advantage over the resistant strain but not with the near-isogenic resistant strain were reported in resistance to malathion in C. ferrugineus (White and Bell 1990) and Bt toxins (Cry1F) in the fall army worm, Spodoptera frugiperda (J.E.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations